High temperature and pressure impact on volume of Ore deposits; itagunmodi gold deposit, South West Nigeria as a case study (2012)
An understanding of the Earth’s interior depends on information about the behavior and properties of matter under high pressures and temperatures. An equation of state that connects pressure (P), volume (V), and temperature (T) is very important. This work examines the impact of high temperature and pressure on the formation and maturity of sediment-hosted disseminated gold (SHDG) deposits in Itagunmodi, Osun State, Nigeria located in the clayey soil types derived from variably migmatised gneiss, biotite-and-biotite-homblende- gneiss and weathered amphibolites respectively. The melting temperatures of gold were determined by differential thermal analyses. After application of appropriate correction for the effect of pressure on emf of thermocouples, the melting curves are linear with the isothermal volume of the melting solid to within the precision of the measurement. This melting point of gold at variable high temperature and pressure, if extrapolated could be used as a primary standard for measurements.